MAKNA ZARRAH DALAM KITAB AL-QUR’AN DAN TAFSIRNYA DAN TAFSIR ILMI KEMENAG RI - Nur Metta Chumairoh Azzuhro (UIN Raden Mas Said Surakarta, 2021)
This article discusses zarrah in two perspectives of the interpretation book produced by the Ministry of Religion of the Republic of Indonesia, namely the tahlili interpretation which is named al-Qur’an dan Tafsirnya and the scientific interpretation with the theme of microogranisms. This is deemed necessary considering that the Indonesian Ministry of Religion has three interpretive products with different perspectives. Using the analytical descriptive method, it is found that the Qur’an and it’s interpretation are more focused on explanations that understand the Indonesian people by providing motivation using the reward and punishment method. Meanwhile, the Ministry of Religion’s scientific interpretation focuses more on the explanation and analysis of scientific theories.